Internalization Event Marketing Communication BPCB Banten Lampung Working Area - Mikail Occultisan; Jamaludin Jamal; Hayu Lusiana (Budapest International Research and Critics University, 2023)
One of the impacts of the COVID-19 pandemic has changed the order in marketing communications. BPCB Banten every time it holds an internalization event, it still has to convey a message to the public. The work program is required to be effective and on target. This research is aimed at BPCB Banten in the working area of Lampung. The objective is to identify the Cultural Conservation Internalization Event program by increasing the number of visitors. Using SOSTAC system analysis and 4P marketing mix mix. Findings: all work areas refer to the central BPCB work program, not all work programs in the Lampung region can be implemented. Work programs are implemented according to different demographics, geography, psychographics, location, targets, locations, forms of promotion, supervision, and local culture. It is hoped that this research can maintain the continuity of the work program, as well as increase the number and enthusiasm of the community's wishes through social media, digital marketing, and websites.